Cosmogenic ³⁵S measurements in the Tibetan Plateau to quantify glacier snowmelt - Priyadarshi, Antra; Hill-Falkenthal, Jason; Thiemens, Mark; Zhang, Zhisheng; Lin, Mang; Chan, Chuen-yu; Kang, Shichang (American Geophysical Union, 2014)
The cosmogenic radionuclide ³⁵S (t₁/₂ ~ 87 days) is a unique tracer for high-altitude air mass and has been used extensively to understand stratospheric air mass mixing. In this paper, we investigate if ³⁵S can be utilized as an independent tracer to quantify glacier melt. We report the first measurements of ³⁵S in samples collected from the Tibetan Plateau during 2009–2012 with an aim to interpret ³⁵S in atmospheric particles and their deposition over glacier and snowmelts. Our measurements show that ³⁵S activity in the aerosol phase varies from 116 ± 13 to 2229 ± 52 atoms/m³ resulting in higher values during winter–spring and lower values during summer–autumn. This seasonality is likely due to higher mixing of ³⁵S-rich stratospheric air masses during winter–spring and ³⁵S-poor air masses from the Bay of Bengal during the Asian summer monsoon. The average ³⁵S activity in the Zhadang glacier was found to be 3–8 times higher relative to the nearby lake water. The main source of ³⁵S activity in the Zhadang glacier is atmospheric deposition, whereas both atmospheric deposition and glacier snowmelt are the primary sources in the Nam Co Lake. The focus of this study is to quantitatively determine the spatial and temporal variations in glacier snowmelt. In the future, extensive sampling of aerosols and snow is required for determining ³⁵S in combination with stable oxygen isotopes in sulfate to better understand the glacier melt process and hydrological cycle on the Tibetan Plateau.